A self-healing distributed pervasive health system. (1st January 2013) - Bromuri, Stefano; Schumacher, Michael I.; Stathis, Kostas
In the context of pervasive healthcare systems there is a growing need of services that are constantly available to the patients accessing them. To address this issue, in this paper we present a distributed pervasive infrastructure that is capable of self-healing one or more of its parts when an external event causes a disruption of the service in the areas covered by the pervasive system. We utilise approaches from multi-agent systems (MASs) such as communication, coordination, planning and agent environments to create a distributed system whose emergent behaviour shows the capability to heal itself even if 50% of the system is not functioning due to external causes.